Development of Fertilizer Recommendation of Four Crops Grown Under the Cropping Pattern: Mustardboro- T. Aus- T. Aman in Aez - 8 (Bangladesh Journal of Agricultural Research, 2022)
A field experiment on mustard- boro- T. aus- T. aman cropping pattern was conducted in the soil of Jamalpur (AEZ - 8) during two consecutive years 2014- 2015 and 2015-2016 with the objectives of finding out suitable fertilizer requirements for a four crops pattern mustard- boro- T. aus- T. aman. The experiment was conducted in RARS (AEZ-8), Jamalpur. There were eight treatments in the study viz. T1: 100% soil test based (STB) NPKSZnB, T2: T1 + 25% N, T3: T1 + 25% NP, T4: T1 + 25% NK, T5: T1 + 25% PK, T6: T1 + 25% NPK, T7: 75% of T1, T8: Native fertility. The experiment was laid out in randomized complete block design with three replications. Data revealed that the seed yield of mustard, grain yield boro, T. aus and T. aman were significantly influenced by application of 25% extra NPK consistently. The highest seed yield of mustard and grain yield of boro, T. aus and T. aman was obtained from the T6 treatment where 25% additional NPK was added over the 100% STB. The lowest yield was recorded for the native fertility treatment in both years.Bangladesh J. Agril. Res. 45(2): 113-123, June 2020